If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -7 + -1y = 12 Reorder the terms: -7 + 3y + -1y = 12 Combine like terms: 3y + -1y = 2y -7 + 2y = 12 Solving -7 + 2y = 12 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 2y = 12 + 7 Combine like terms: -7 + 7 = 0 0 + 2y = 12 + 7 2y = 12 + 7 Combine like terms: 12 + 7 = 19 2y = 19 Divide each side by '2'. y = 9.5 Simplifying y = 9.5
| -6(1+3)+5=-1+4x | | 25x=130 | | 12-45(x+15)=4 | | 8x^2-10=40 | | 16+4y-1=17y-9-5y | | -2(c-3)-4=18 | | 25x+84=25x+83x | | 10x+8y+16z=334 | | 8-4-6d=22 | | -x^2+1=5x+1 | | -2y=4x-16 | | (4+7)y+(5+10)= | | 5*2n=17 | | 2x-6+3=25 | | 4(4x+5)=4(3x-1) | | -12x^2=-1200 | | x*2+9=36 | | 6x^2-18=6+18x | | 9j+8j= | | Y-4+3=70 | | 3x+12+2x+6+x= | | 2.5-0.03=-0.02 | | 9*16=a | | 4y-6y+12=46 | | 5(-2+5)-15=100 | | -41*1=12 | | ProveAC=32 | | -27+2=73 | | AC=32 | | 4(34)-1= | | 4x-x+2=16-8 | | 3.5-0.04=-1.74 |